Car Security - Vehicle Theft Identity and Control System - Alex, NV; Mathew, Filma (International Journal of Computer Sciences and Engineering, 2015)
Due to the insecure environment the ratio of vehicle theft increases rapidly. Because of this is manufacturers of luxury automobiles has the responsibilities for taking steps to ensure the authorization for the owners and also in built the anti theft system to prevent the vehicle from theft. The proposed security system for smart cars used to prevent them from loss or theft using FIM 5360 and PIC16F877A processor. It performs the real time user authentication using face recognition and finger print detection. According to the comparison result, processors trigger certain actions. If the result is not authentic means processors produces the signal to block the car access. It produce the interrupt signal to car engine to stop its action, alarm and inform the car owner about the unauthorized access via SMS and sends image to owners mailbox with the help of GSM modem.